2000
DOI: 10.1093/nar/28.8.1707
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repression by the insulator protein CTCF involves histone deacetylases

Abstract: The highly conserved zinc-finger protein, CTCF, is a candidate tumor suppressor protein that binds to highly divergent DNA sequences. CTCF has been connected to multiple functions in chromatin organization and gene regulation including chromatin insulator activity and transcriptional enhancement and silencing. Here we show that CTCF harbors several autonomous repression domains. One of these domains, the zinc-finger cluster, silences transcription in all cell types tested and binds directly to the co-repressor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
121
2
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(130 citation statements)
references
References 52 publications
6
121
2
1
Order By: Relevance
“…SIN3A is a transcriptional regulator belonging to the Sin3-histone deacetylase core complex (25,26). Notably, SIN3A protein has conserved motifs that bind to the chromatin insulator protein CCCTC-binding factor (CTCF), a ubiquitously expressed, highly conserved transcriptional repressor that recruits SIN3A and other proteins to the promoters of target genes (27,28). Importantly, the CFTR locus contains functional CTCF-binding sites (29).…”
Section: Resultsmentioning
confidence: 99%
“…SIN3A is a transcriptional regulator belonging to the Sin3-histone deacetylase core complex (25,26). Notably, SIN3A protein has conserved motifs that bind to the chromatin insulator protein CCCTC-binding factor (CTCF), a ubiquitously expressed, highly conserved transcriptional repressor that recruits SIN3A and other proteins to the promoters of target genes (27,28). Importantly, the CFTR locus contains functional CTCF-binding sites (29).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism by which CTCF prevents transcription may involve the binding of SIN3A and associated HDACs to an internal 11 Zn fingercontaining region of CTCF and possibly additional corepressors to the C-terminus. 44 There may be additional mechanisms by which DNA methylation affects transcription. In vitro studies have shown that methylation at cytosine residues can cause several changes in DNA structure (reviewed in 45 ).…”
Section: Methylation and Transcriptionmentioning
confidence: 99%
“…3 Ctcf regulates chromatin architecture together with cohesion proteins, which are enriched at Ctcf-binding sites. [5][6][7] In addition, multiple functions of Ctcf are enabled by interaction with different binding partners like transcription factors (Yy1, Kaiso and YB-1), [8][9][10] chromatin modifying proteins (Sin3a, CHD8, Suz12), [11][12][13] RNA polymerase II 14 and poly(ADP-ribose) polymerase-1. 15 Recently, Ctcf was found to control MHC class II gene expression, 16 and it was reported that enforced overexpression of Ctcf in DC caused increased apoptosis, reduced proliferation and impaired differentiation.…”
Section: Introductionmentioning
confidence: 99%